(untitled) (Jurnal Kemanusiaan, 2018)
Counseling services have been widely developed in universities. However, there is still a lack of research that is focused on the factors pertaining to studentsâ€™ willingness to seek counseling services. Therefore, this study was conducted to identify factors related to the students’ willingness to seek counseling services using the Cramer Model (1999). The questionnaires which measured the social support (Cutrona & Russell, 1987), self-concealment (Larson & Chastain, 1990), stress (Green et al., 1988) and attitude towards counseling (Fischer & Farina, 1995) were employed to evaluate 118 third-year students from the Faculty of Management, UTM who were selected through a randomized sampling. The results of the study showed that each factor related to the willingness of students to seek counseling services (social support, self-concealment, stress, and attitudes towards counseling) is at a low level. However, the most dominant factor regarding the studentsâ€™ willingness to seek counseling services at UTM Skudai is self-concealment. Meanwhile, there was no significant difference in social support, self-concealment, stress and attitudes factors in relation to counseling among the students based on gender. This study concludes with the implications as well as the recommendations for future works for researchers.